Cooking methods and determination of the nutritional content of tilapia (oreochromis sp) (LACCEI, 2024)
The objective of this study was to determine the different cooking methods on nutritional properties of Tilapia fish (Oreochromis ps) and two physiochemical parameters (wáter activity aw and pH). A completely randomized experimental design with two replicas with three repetitions was used, the treatments were: electric oven at 60 and 80ºC, vapor at 60 and 80ºC, and microware at 140 and 1400 Watts and the response variable were: protein, lipids, ash, moisture, aw and pH contents. For the statistical analysis of data, an analysis of variance was used and the mean values were compared using the Tukey test (P0.05). The proximal compositions of the Tilapia fish were: protein 22.16 ± 0.04%, lípidos 1.3 ± 0.01%, cenizas 1.14 ± 0.008% y humedad 78.11 ± 0.18%. The values of the physiochemical parameter were: wáter activity of 0.98 ± 0.008 y pH de 6.64 ± 0.008. The proximal compositions and physiochemical parameter were significantly affected (P0.05). The best treatments for the conservation of proteins were microwave at 140 and 1400 watts, and the method that most greatly decreased proteins was the oven at 80ºC. On the other hand, there was decrease of fat in the vapor treatment at 60ºC and in the microware treatment at 140 watts compared with electric oven treatment at 60 and 80ºC. The application of cooking methoda in the microware (140 and 1400 Watts) and vapor (60ºC) there were more protein bands, compared with the electric oven (60 y 80ºC) and vapor (80ºC). The electric oven treatment (60 y 80ºC) showed fewer protein bands. This information is useful to enrich data from chemical composition tables, in which concentrations are usually presented in raw food.